Implementation of Learning and Fundamental Motor Skill Measurement of Early Childhood Motor Skill for PAUD Teachers in Padang Panjang City - Syahrial Bakhtiar; Zainul Johor; Oktarifaldi Oktarifaldi; Lucy Pratama Putri (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2019)
esearch shows that physical activity of children at an early age will greatly trigger the development of cognitive abilities. Based on observations and studies in the field, it was found that almost all teachers and educators in PAUD Padang Panjang did not have the skills in designing learning and evaluating the basic movements of children. Based on research, basic motion cannot develop naturally but must be taught correctly and continuously. The learning material to be realized must be based on the child's initial ability and level of movement skills. This community service activity for partners aims to: (a) possess skills in designing fundamental motor skills learning, (b) understand and be skilled in using early childhood fundamental motor skill measurement instruments, (c) able to effectively implement learning in school places respective agencies. The method used uses the principle that every innovation received by PAUD teachers through PIE (Preparation, Implementation and Evaluation). This means that the delivery of innovations to Partners is carried out through the stages of explanation, discussion, practice as well as the evaluation stage with assistance in the learning process. Based on the implementation of the training, the results obtained for PAUD teachers in Padang Panjang as training participants can be described as follows: (a) has the skills in designing fundamental motor skill learning, (b) understanding and skilled in using fundamental motor skills measurement instruments for early childhood, (c) able to effectively implement learning in their respective school offices.